A Total systems study on Furniture Company - Cancio, John Michael; Lavin, Caitlin Mae; Peñalosa, William Albert; Reyes, Richmond Ryan (College of Engineering, 2003)
Furniture Company is a retailer of fine home furniture. The company carries an assortment of products from a wide range of suppliers and offers them at reasonable prices while providing customer service. The mission of the company is to be the leader, the best and the most profitable home furniture chain store nationwide. The practices of Furniture Company were documented and from here, problems, strengths, weaknesses, opportunities and threats were identified. Analysis of the strengths, weaknesses, opportunities and threats of Furniture Company revealed that the currently opened distribution center presented many good opportunities to improve the system. The opportunity for system improvement arises from the new system of operating the distribution center that is considered for implementation. This new system will affect the capacity of the distribution center in terms of floor space, manpower and trucking. Aside from this great opportunity, the analysis also revealed the weaknesses of the current system such as the absence of a formal inventory system. The documentation and analysis of the current practices of Furniture Company revealed problems in forecasting, inventory management and capacity planning. For the problem in forecasting, it was suggested that the company change the forecasting technique from simple moving average to exponential smoothing with an alpha of 0.3. The inventory management system is solved by implementing a reorder point inventory system with a 99.99% cycle service level. The problem on capacity is then solved by computing for the required capacity of the new system based on the results of the reorder point inventory system previously developed. The computations and analysis show that the capacity of the distribution center in terms of manpower, space and trucking is enough to meet the requirements of the proposed system for the distribution center. Cost-benefit analysis was then used to determine if the proposed distribution center is beneficial. The analysis shows that the implementation of the proposed system will increase customer satisfaction and sales as well as save the supplier money, decrease environmental pollution, result to an increasing return on investment and reduce the payback period of the new distribution center. The benefits of the implementation of the proposed system clearly outweigh the costs of implementing the system and it was therefore recommended that the new system be implemented.